Comparative Analysis of Forecasting Performance : Crude Palm Oil Futures (CPO) Prices vs Expert Opinions - Ahmed, Abdullahi Farah (2001)
The main economic functions of the futures market are to provide price discovery and risk management facilities. It is well known that the futures market can function well only when the futures prices provide accurate price forecast to subsequent cash prices. The greater the degree of price forecast accuracy, the greater the effectiveness of the futures market in terms of performing its economic functions. If the market is not efficient, effective transmission of information from one market to another will be impaired, thus the value of the futures market in price discovery and hedging. The creation of the crude palm oil (CPO) futures market in Malaysia was to fulfil the need for an efficient pricing and hedging mechanism for Malaysia's palm oil. Therefore, the extent to which CPO futures market has served as an efficient center of price discovery and risk management, has been the focus of considerable research. In general, debate has centered around the extent of which futures market provide price leadership to cash market and the ability of futures market to predict subsequent spot debate has centered around the extent of which futures market provide price leadership to cash market and the ability of futures market to predict subsequent spot price in accurate way. Empirical evidence has shown that CPO futures prices performed relatively better compared to other forecasting models. However, no comparison is made in forecast accuracy of CPO futures with expert opinion. This approach is unique in the sense that it examines the relative efficiency of ex ante forecasts rather then ex post. The objectives of this study are: firstly, to evaluate the forecast accuracy of the CPO futures market relative to expert prediction. Secondly, to test the relationship between the futures, forward and cash prices, to examine whether these price series have the same properties and relationship in the long-run. AGS and the Johansen's cointegrations techniques were used to analyze the forecast accuracy and log-run relationship over, 1st, tld, 3rd and 4th month spreads offutures and forward prices. The analyzed sample data consists of the daily end-of-month trading prices of the futures, cash, and forward prices for the period from January 1 989 to December 1 999. The findings of this study suggested that the forward forecast accuracy price was superior to the futures. It implies that the forward prices which represent expert prediction of cash price, contain more information for price discovery than CPO futures prices in the one month and two months horizons. This finding indicated that the CPO of futures market is relatively less efficient. Hence, the use of futures prices for short-term price forecasting may be more biased than relying on expert forecasts.